Prediction of Pelvic Inclination in the Sitting Position after Corrective Surgery for Adult Spinal Deformity - Daisuke Nishiyama; Hiroshi Iwasaki; Takuhei Kozaki; Takaya Taniguchi; Wataru Taniguchi; Teiji Harada; Hiroshi Yamada (Spine Surgery and Related Research, 2020)
Introduction: Hip dislocation rates in patients with combined total hip arthroplasty (THA) and spinal deformity fixation are significantly higher than those of THA alone. Nevertheless, there are no treatment recommendations for patients who undergo THA and require a spine deformity correction later. Methods: Twenty-eight patients underwent spinal fixation surgery for adult spinal deformity. Sagittal spinopelvic alignment was analyzed on lateral radiographs taken preoperatively and postoperatively in the sitting and standing positions. Univariate linear regression analysis was conducted to identify the factors affecting the pelvic inclination in the sitting position after spinal fixation. Multiple regression analysis was conducted to determine the most efficient combination of radiographic parameters for predicting postoperative pelvic inclination while sitting. Results: There were significantly weak associations between postoperative sacral slope (SS) in the sitting position and the following factors: the number of vertebral levels fused (β = 0.30, p = 0.003); the presence of sacral fixation (β = 0.22, p = 0.01); the presence of sacroiliac joint fixation (β = 0.24, p = 0.008); and preoperative SS while standing and sitting (β = 0.21, p = 0.01 and β = 0.34, p = 0.001). Postoperative lumbar lordosis (LL) while standing was strongly associated with postoperative SS in the sitting position (β = 0.67, p <.0001). The combination of postoperative LL in the standing position and preoperative SS in the sitting position was the best fit, and the adjusted R-squared was 0.82. Conclusions: We devised a prediction formula for pelvic inclination while sitting after spinal fixation that has high predictability: postoperative SS while sitting = 11.7+ (0.4 × postoperative planned LL while standing) + (0.16 × preoperative SS while sitting). This study could be the basis for treatment recommendations for patients who have undergone THA and require a spine deformity correction later.